ANALYSIS OF MARKETING STRATEGY IMPLEMENTATION GUIDANCE SERVICES IN IMPROVING STUDENTS LEARNING (Case in Tutoring Primagama Branch Institute Panam, Pekanbaru) - Patama, Jefta; zuli, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the marketing strategy implementation tutoring services in improving learners at LBB Primagama Branch Panam, Pekanbaru. The number of samples of this study are as many as 50 students. As this study used a questionnaire with a scale of measurement using a Likert scale.The research results are made known that the implementation of the marketing strategy LBB Primagama Branch Panam, Pekanbaru consists of marketing mix is a product of education services, education price, promotion, location, and the overall well categorized.Keywords: Marketing Strategies, Services, Education